How to Read Job - Walton, John H., 1952- (Downers Grove, Illinois : IVP Academic, 2015)
We often turn to the book of Job when we encounter suffering. We look for an explanation for the questions "Why me?" or "Why her?" But what if it turns out that although Job does suffer, the book is not really about his suffering? If ever a book needed a "How to Read" instruction manual, it is the book of Job. And when two respected Old Testament scholars team up -- both of whom have written commentaries on Job -- we have a matchless guide to reading and appreciating the book. From their analysis of its place in the wisdom literature of the Bible and the ancient Near East to their discussions of its literary features and relationship to history, Walton and Longman give us the best of their expertise. They explore the theology of Job, placing it within Israelite religion and Old Testament theology. And they coach us in how to read Job as Christians. When it turns out the book is not what we thought it was, our reading is richly layered and more satisfying. Whether you are preparing for preaching, teaching, leading a Bible study, studying for a class or for personal enrichment, How to Read Job is your starting point. - Publisher.
Part one : Reading Job as literature. What is the Book of Job about? -- What is the rhetorical strategy of the Book of Job? -- Job in the context of the ancient Near East -- Is Job a real person? -- Part two : Getting to know the characters of the Book of Job. What do we learn about God from the Book of Job? -- Who is "Satan" in Job? -- What is the role of Job in the Book of Job? -- How to assess Job's human advisers -- Who is Job's advocate? -- Behemoth and Leviathan, the most powerful creatures imaginable -- Part three : The theological message of the Book of Job. The retribution principle and theodicy in Job -- The retribution principle in wisdom literature -- Does Job believe in the afterlife? -- Learning about the cosmos from the Book of Job -- The theology of suffering in the Book of Job -- Job's view of God -- Part four : Reading Job as a Christian. Job and Jesus -- The message of the Book of Job for today -- Does the Book of Job provide comfort? -- Applying the Book of Job -- Appendix : Commentaries on the Book of Job.
Includes index.
Includes bibliographical references (pages [191]-202) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics; Criticism, interpretation, etc